2019
DOI: 10.17755/esosder.362659
|View full text |Cite
|
Sign up to set email alerts
|

Li̇sans Öğrenci̇leri̇ni̇n Erasmus Öğrenci̇ Öğreni̇m Hareketli̇li̇ği̇ Programi’na İli̇şki̇n Farkindaliklari Ve Tutumlari

Abstract: Bu çalışmanın amacı, Lisans Öğrencilerinin Erasmus Öğrenci Öğrenim Hareketliliği Programı'na ilişkin farkındalık düzeylerini belirlemek ve tutumlarını farklı değişkenler açısından ortaya koymaktır. Araştırma evrenini 2015-2016 eğitim öğretim yılında Necmettin Erbakan Üniversitesi Ahmet Keleşoğlu Eğitim Fakültesindeki lisans öğrcncileri oluştururken, örneklem Fakültenin dokuz farklı bölümde öğrenim gören toplam 724 lisans öğrencisinden oluşmaktadır. Yapılan çalışmanın sonucunda, lisans öğrencilerin Erasmus Öğre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…In this research, it is seen that university students are aware of the Erasmus+ exchange program in various ways. A study conducted on the awareness of undergraduate students about the Erasmus program revealed that approximately 77% of the undergraduate students participating in the study had insufficient knowledge about the Erasmus+ exchange program (Saban et al, 2019). To provide more information about the Erasmus+ exchange program and reach more students, it is recommended that the Erasmus Coordinatorships organize an orientation for the new university students about the Erasmus+ exchange program and to introduce students to this program earlier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, it is seen that university students are aware of the Erasmus+ exchange program in various ways. A study conducted on the awareness of undergraduate students about the Erasmus program revealed that approximately 77% of the undergraduate students participating in the study had insufficient knowledge about the Erasmus+ exchange program (Saban et al, 2019). To provide more information about the Erasmus+ exchange program and reach more students, it is recommended that the Erasmus Coordinatorships organize an orientation for the new university students about the Erasmus+ exchange program and to introduce students to this program earlier.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are studies on various aspects of the Erasmus+ exchange program. These studies include the studies dealing with students' level of satisfaction with the program (Yagcı, Ekinci, Burgaz, Kelecioglu & Ergene, 2007), student awareness and attitudes towards the program (Saban, Cenberci & Cenberci, 2019), the effects of the program on students (Onder & Balci, 2010), students' views on classroom management in the country they went (Boyaci, 2011), evaluating the program concerning dialogue and interaction in cultural dimensions (Demir & Demir, 2009), and problems faced by students in the process (Ersoy, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Şerhedilmiş kişisel hak aynî hak olmadığı içindir ki, örneğin taşınmaza bir haksız fiil neticesinde zarar verildiğinde kişisel hak sahibinin failden tazminat talep edebilmesi mümkün değildir 28 . adına tescilini istemesi mümkün hâle gelmektedir 40 . Bunun yanında, taşınmaz üzerinde şerhten sonra hak kazanan ve satış vaadinden doğan borcun ifasına engel olan sınırlı aynî hak sahipleri ile şerhedilmiş kişisel hak sahiplerinin haklarının da etkisizleştirilmesi sağlanabilmektedir 41 .…”
Section: şErhin Etkisiunclassified
“…IV adına tescilini istemesi mümkün hâle gelmektedir 40 . Bunun yanında, taşınmaz üzerinde şerhten sonra hak kazanan ve satış vaadinden doğan borcun ifasına engel olan sınırlı aynî hak sahipleri ile şerhedilmiş kişisel hak sahiplerinin haklarının da etkisizleştirilmesi sağlanabilmektedir 41 .…”
Section: şErhin Etkisiunclassified